The nature of economic growth : an alternative framework for understanding the performance of nations - Thirlwall, A. P. (Cheltenham ; Northampton, MA : E. Elgar, 2002)
This text charts development economics as it evolved from Adam Smith to "new" or endogenous growth theory. Thirlwall is critical of the latter, and its predecessor neo-classical growth theory, and tries to put back demand as a driving force in growth theory.
Includes bibliographical references (p. 97-105) and index.
oif 18/09/15
Loan
Keywords: Economic development